Solve this


Solve for $x: x^{2}-5 i x-6=0$


We have, $x^{2}-5 i x-6=0$

Here, $b^{2}-4 a c=(-5 i)^{2}-4 \times 1 \times-6$

$=25 i^{2}+24=-25+24=-1$

Therefore, the solutions are given by $\mathrm{x}=\frac{-(-5 \mathrm{i}) \pm \sqrt{-1}}{2 \times 1}$

$x=\frac{5 i \pm i}{2 \times 1}$

$x=\frac{5 i \pm i}{2}$

Hence, x= 3i and x = 2i


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now